Time decay of stable absorption of gamma irradiated lithium niobate crystals doped by cuprum ions - Potera, Piotr (Proceedings of International Conference Oxide Materials for Electronic Engineering 2012, pp 165-166, 2012)
The transient and stable color centers in pure and doped lithium niobate crystals (LNO) have been investigated in several works, for example in [1]. The stable color centers are centers which have lifetime higher then 1s. Unfortunately, the lifetime of color centers were studied in literature only for transient color centers, for example in [2]. In this work the lifetime of stable additional absorption induced by gamma irradiation in Cu doped of LNO crystal will be determined from data obtained during 10 years.
Keywords: gamma irradiation; color centers